The trade-off between monetary and fiscal solidity: International lenders and political instability - Frank Bohn (University College Dublin, Department of Economics, 2004)
This paper analysis the intertemporal public finance decision under political instability. The government's choice between inflationary finance and foreign debt is constrained by an interest rate, which is affected both by market conditions and debt conditionality. The main result is that there is typically a trade-off between seigniorage taxation and foreign debt. There are two implications. First, monetary and fiscal solidity can typically not be achieved at the same time. Second, myopic behaviour produced by political instability leads to a reduction of seigniorage, not to an increase as argued, for instance, by Cukierman, Edwards and Tabellini (AER, 1992).
hdl:10197/1788
Keywords: E63; F34; O23; 330; debt conditionality; myopic behaviour; political economy; seigniorage; government deficit; public finance